European Bioanalysis Forum: recommendation on dealing with hemolyzed and hyperlipidemic matrices. (December 2014) - Ingelse, Benno; Barroso, Begona; Gray, Nicholas; Jakob-Rodamer, Verena; Kingsley, Clare; Sykora, Corinna; Vinck, Petra; Wein, Martina; White, Stephen
Recent guidelines on bioanalytical method validation have recommended to investigate matrix effects in special matrices such as hemolytic and hyperlipidemic plasma. However, these guidelines were not clear on how to implement these recommendations. The European Bioanalysis Forum has discussed this topic in depth and has asked for feedback from member companies. Those discussions have resulted in more specific guidance on how to define hemolytic and hyperlipidemic plasma, how to validate bioanalytical methods for these matrices and how to deal with hemolytic and hyperlipidemic study samples. These recommendations are presented in this manuscript.